(untitled) (Journal of the College of Basic Education, 2023)
The research aims to evaluate and classify the suitability of current and future soil characteristics for autumn sugar beet cultivation in the North Island Irrigation Project, using geographic information systems. Land suitability is the suitability of a specific area of ​​land for a specific use. As for the classification of land suitability, it is the evaluation and grouping of specific areas of land that are similar in their suitability for a specific use. To determine the best or suitable location for autumn sugar beet cultivation, which makes an optimal investment of land resources in a sustainable manner. By building spatial and descriptive databases (data bank), through a survey and inventory of land resources, land characteristics, requirements and determinants for sugar beet cultivation in the study area,